BEBERAPA ASPEK PENTING DALAM PENILAIAN PENGELOLAAN PASCA PEMANENAN DI HUTAN TANAMAN - Endom, Wesman; Nitibaskara, Tb. Unu (Jurnal Nusa Sylva, 2015)
Biomass of timber post forest harvest (natural forest or made man forest0 that available at the felling site is one of natural sources which have a volume still potentially. These materials can be use for energy sources or fulfil of additional materials for pulp and paper industries or another product as availability of volume, type and seize of biomass which usually called as wastes. This potency can be obtained from plantation forest and or natural forest especially on conversion forest production in the form of wastes of bucking, trimming, main stem, branch and stump. The problem is how to collect it in an effective and efficient way. The availability of wood wastes among other due to other function has high condition, particularly for plywood and timber construction as well. For example the length of wood to short, to small of diameter, many defect, decay and holes or bending. Other form are stump and roots, branches and to many bandings. Mostly all of wood wastes are used for layer when equipment wills passing that rows. Similar thing can also obtain from limb trees hit by tree which is cut, hit on skidding operation and road construction.Â